2007
DOI: 10.1136/gut.2006.107946
|View full text |Cite
|
Sign up to set email alerts
|

Post-load insulin resistance is an independent predictor of hepatic fibrosis in virus C chronic hepatitis and in non-alcoholic fatty liver disease

Abstract: Post-load insulin resistance (OGIS <9.8 mg/kg/min) is associated with severe hepatic fibrosis in both NAFLD and CHC patients, and may help identify subjects at risk of progressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 45 publications
7
71
0
1
Order By: Relevance
“…Original magnification !400. (16), one could expect fetuin A, as a marker of insulin resistance, to increase in parallel with the degree of liver fibrosis. On the other hand, fetuin A is a known extracellular inhibitor of transforming growth factor b (17), the key profibrogenic stimuli in chronic liver disease (18).…”
Section: Discussionmentioning
confidence: 99%
“…Original magnification !400. (16), one could expect fetuin A, as a marker of insulin resistance, to increase in parallel with the degree of liver fibrosis. On the other hand, fetuin A is a known extracellular inhibitor of transforming growth factor b (17), the key profibrogenic stimuli in chronic liver disease (18).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that insulin resistance is associated with interferon signalling, which plays an important role in the clearance of chronic hepatitis C (CHC) during interferon therapy (4,5). Previous studies have demonstrated the association between metabolic syndrome and hepatic fibrosis in patients with hepatitis C (6)(7)(8)(9)(10)(11). Steatosis is a frequent histological finding in chronic hepatitis C virus infection, one that affects disease progression and occurrence of hepatocellular carcinoma (7,(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy with PegIFN and ribavirin has been recommended as standard therapy for patients with HCV infection with favorable efficacy (Hui et al, 2003;Petit et al, 2001;Svegliati-Baroni et al, 2007). It therefore provides a wide scope of view addressing the correlation between HCV infection and IR.…”
Section: The Characteristics Of Glucose Abnormalities In Patients Witmentioning
confidence: 99%
“…The prevalence of the MS in patients with CHC varied from 4.4% in Italy, 24.7% in Taiwan and 51% in US veterans (Huang et al, 2009a;Keane et al, 2009;Svegliati-Baroni et al, 2007), suggesting that host factors such as ethnic origin could play a role in the association between IR and CHC (Conjeevaram et al, 2007;Serste et al, 2010). Liangpunsakul et al examined the relationship between nondiabetic subjects with HCV infection and microalbuminuria by using NHANES III database which consisted of 15,336 adults from the United States.…”
Section: Metabolic Disordersmentioning
confidence: 99%
See 1 more Smart Citation